Decomposition and comparative analysis of urban-rural disparity in attitude towards advance care planning among Chinese adults: A nationwide study - Xue Wang; Yibo Wu; Lina Ge; Meizhen Zhao; Yi Ma; Shuang Zang (BMC Public Health)
Abstract Background Examining urban-rural disparity in Chinese adults’ advance care planning (ACP) attitudes is crucial for healthcare decision-making. A comprehensive understanding of contributing factors, especially through decomposition and comparative analysis, remains limited. Methods Data were derived from Psychology and Behavior Investigation of Chinese Residents (PBICR) including 19,738 participants, representative of Chinese adults. We constructed multivariate linear regression models to investigate the primary factors influencing the attitudes toward ACP among Chinese adults. Additionally, we employed Blinder-Oaxaca decomposition to analyze the factors contributing to the urban-rural disparities in ACP attitudes among Chinese adults and their respective contributions. The STROBE checklist was used in reporting this study. Results The mean acceptance scores for ACP were 64.83 (standard deviation (SD) 25.83) among urban Chinese adults, significantly surpassing the scores observed in rural areas, which were 61.71 (SD 25.57) (p < 0.001). Blinder-Oaxaca decomposition analysis indicates that 98% of the urban-rural disparity in ACP attitudes among adults can be explained. This disparity is primarily associated with differences in household per capita monthly income (31.55%), health literacy (31.25%), education level (18.71%), age (-15.12%), family health (13.95%), perceived social support (10.48%), and self-efficacy (7.46%). Conclusions The findings suggest policymakers should enhance ACP education in rural areas to reduce disparities. Clinically, tailored ACP discussions and integration into routine care can improve acceptance, particularly in underserved regions.